2019
DOI: 10.1002/lipd.12185
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Fatty Acid Biomarkers of Dairy Intake across Serum Lipid Fractions: The Prospective Metabolism and Islet Cell Evaluation (PROMISE) Cohort

Abstract: Circulating fatty acids (FA) derived largely from dairy consumption have most commonly been measured in total human serum or phospholipid (PL) fractions, and have been used as validated biomarkers of dairy intake in a growing number of epidemiological studies. Nevertheless, measurement and characterization of a wider spectrum of FA biomarkers of dairy across the four major serum lipid fractions is lacking. This study aimed to (1) quantify FA biomarkers of dairy in PL, triacylglycerol (TAG), cholesteryl ester (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…However, the underlying mechanisms are largely unknown. Previous studies have suggested that circulating C15:0 could be regarded as a direct biomarker of dietary C15:0 intake (Gotoh et al, 2008 ; Hodson et al, 2008 ; Jenkins et al, 2017 ; Rezanka & Sigler, 2009 ; Santaren et al, 2019 ), whereas circulating C17:0 is a product of biosynthesis, which can be affected by and correlates with dietary substrate intake (Jenkins et al, 2017 ). Even‐numbered chain‐length saturated fatty acids are mainly derived from de novo lipogenesis, through which carbohydrates and alcohol are converted to fatty acids in the liver or adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms are largely unknown. Previous studies have suggested that circulating C15:0 could be regarded as a direct biomarker of dietary C15:0 intake (Gotoh et al, 2008 ; Hodson et al, 2008 ; Jenkins et al, 2017 ; Rezanka & Sigler, 2009 ; Santaren et al, 2019 ), whereas circulating C17:0 is a product of biosynthesis, which can be affected by and correlates with dietary substrate intake (Jenkins et al, 2017 ). Even‐numbered chain‐length saturated fatty acids are mainly derived from de novo lipogenesis, through which carbohydrates and alcohol are converted to fatty acids in the liver or adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A known amount of heptadecanoic acid (17:0) in FFA, TG, PL, and CE form were added to serum, as an internal standard, prior to extracting total lipids according to the method of Folch (Folch et al, 1957). Thin layer chromatography G-plates were loaded with a portion of the total Santaren, 2019). BCFA standards were methylated and analyzed via GC-FID (iso14:0, anteiso14:0, iso15:0, anteiso15:0, iso16:0, iso17:0, anteiso17:0, and iso18:0 purchased from Larodan AB in Solna, Sweden).…”
Section: Fatty Acid Measuresmentioning
confidence: 99%
“…The δ13C reporting unit is milliUrey (mUr). A 1 mUr change equals to a 0•1 % (or 1‰) change in 13 C: 12 C compared with a reference material. Therefore, a positive delta δ13C value is indicative of an increase in δ13C.…”
Section: Carbon 13 Isotopic Analysis Reporting and Normalisationmentioning
confidence: 99%
“…When compared to most vegetable oils and margarines, dairy fat contains very low amounts of the omega-6 polyunsaturated fatty acid (n-6 PUFA) linoleic acid (18:2n-6), the major dietary PUFA in the western style eating pattern (9). Some fatty acids have been proposed as markers of dairy intake such as 15:0 and 17:0 (10)(11)(12)(13)(14). Serum levels of these fatty acids have been associated with a lower risk of developing CVD (15) and type 2 diabetes (16) in adults.…”
Section: Introductionmentioning
confidence: 99%